Art and mental health in the women's psychiatric intensive care unit. (1st April 2020) - Butler, Sophie; Adeduro, Ronnie; Davies, Rebecca; Nwankwo, Onyekachi; White, Niamh; Shaw, Timothy; Skelton, Luke; Shannon, Geordan; Smale, Emma; Corrigan, Marie; Martin, Daria; Sethi, Faisil
It is widely acknowledged in hospitals that the quality of design and environment can influence the quality of patient care, the sense of therapeutic security and the experience of staff. This women's PICU collaborated with the charity Hospital Rooms to realise the valuable role of art within the clinical environment. Experienced artists were commissioned to work in genuine partnership with patients and staff to re-envision the physical environment with the installation of eight imaginative, inventive and PICU compliant art works; The implementation, and both patient and staff perspectives were evaluated. There was no disruption to clinical care and engagement and participation was enthusiastic. There were 35 patient encounters and 32 staff encounters, including creative workshops and an exhibition; Patient Experience Data Intelligence Centre (PEDIC) reports showed an improvement following artwork installation. Patients were more likely to recommend the ward, felt more involved in their care and that the ward was comfortable. The art transformed clinical spaces creating opportunity for patients to have exceptional experiences: 'being here feels like sitting in the park'; Staff evaluation through a 'visual matrix' method that explores shared experience, revealed that the art has introduced further possibility of 'respite and escape' for both patients and staff. There is a sense that 'you feel like it is leading you to somewhere, you feel like there is something more'. It has also engendered 'ownership and pride': it 'feels like pushing boundaries, things you thought could never be considered at all, are now being considered'.